Study of wakefields in longitudinally and transversely inhomogeneous rectangular dielectric resonators - Markov, P.I.; Kiselev, V.A.; Kniaziev, R.R.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2014)
At Institute of Plasma Electronics and New Methods of the Acceleration of NSC KIPT the experimental inspection of the principles of creation of multi-bunch and the multimode wakefield dielectric accelerator is carried out. For clearing up of the physical processes arising in case of excitation the wakefield and dynamics of electron bunches in such accelerator we executed a series of analytical and numerical calculations, and also full three-dimensional simulation by means of the developed 3D code is carried out. Wakefields were excited in case of injection of sequence of electron bunches in a rectangular vacuum wave guide of R32 type (72.14 ×34.04 mm) or R26 type (86.36 ×43.18 mm), filled with dielectric with the relative dielectric permittivity ε = 3.8, covering two opposite wide walls of a waveguide. The bunch repetition frequency was 2,805 GHz, energy of electrons was 4.5 MeV, average current was 0.73 A and a charge of one bunch was 0.26 nC. The electron bunches arriving through an open input end of a dielectric waveguide were deviated by a cross magnetic field of permanent magnets to a metal wall of waveguide free of dielectric. Depending on the location of magnets along a structure axis the length of interaction of electron bunches with a dielectric waveguide varied. Experimentally the linear dependence of the electric field value excited by bunches, near an output end of a semi-limited dielectric waveguide versus the interaction length is found. The 3D modeling executed by us researched possibility of the growing dependence of amplitude of a longitudinal electric field found in experiment at an output end of a waveguide from interaction length. The chronology of longi-tudinal electric field near output end on axis of system was probed and it spectral characteristic were analyzed too. The carried out researches allowed to better understanding the physical processes happening in the wakefield dielectric accelerator. В ХФТИ выполнена экспериментальная проверка принципов создания многосгусткового и многомодового кильватерного диэлектрического ускорителя. Кильватерные поля возбуждались при инжекции последовательности электронных сгустков в прямоугольном вакуумном волноводе типа R32 (72,14×34,04 мм) или типа R26 (86,36×43,18 мм), заполненном диэлектриком с относительной диэлектрической проницаемостью ε = 3.8, покрывающем две противоположные широкие стенки волновода. Частота повторения сгустков составляла 2,805 ГГц, энергия электронов была 4,5 MэВ, заряд одного сгустка составлял 0,26 нКл. Электронные сгустки, поступающие через открытый входной торец диэлектрического волновода, отклонялись поперечным магнитным полем постоянных магнитов к металлической стене волновода, свободной от диэлектрика. В зависимости от расположения магнитов вдоль оси структуры изменялась длина взаимодействия электронных сгустков с прямоугольным диэлектрическим волноводом. Выполненное нами 3D-моделирование показало линейный рост амплитуды продольного электрического поля на выходном торце волновода с длиной взаимодействия, что находится в хорошем соответствии с экспериментально полученной зависимостью. Исследовались хронологические зависимости продольного электрического поля вблизи выходного торца волновода на оси системы, получены и проанализированы спектральные характеристики колебаний поля. Проведенные исследования приводят к лучшему пониманию физических процессов, происходящих в кильватерном диэлектрическом ускорителе. У ХФТІ виконана експериментальна перевірка принципів створення багатозгусткового й багатомодового кільватерного діелектричного прискорювача. Кільватерні поля збуджувалися при інжекції послідовності електронних згустків у прямокутному вакуумному хвилеводі типу R32 (72,14×34,04мм) або типу R26 (86,36×43,18 мм), заповненому діелектриком з відносною діелектричною проникністю ε = 3.8, що покриває дві протилежні широкі стінки хвилеводу. Частота повторення згустків становила 2,805 ГГц, енергія електронів була 4,5 MеВ, заряд одного згустка становив 0,26 нКл. Електронні згустки, що надходили через відкритий вхідний торець діелектричного хвилеводу, відхилялися поперечним магнітним полем постійних магнітів до металевої стіни хвилеводу, вільної від діелектрика. Залежно від розташування магнітів уздовж осі структури змінювалася довжина взаємодії електронних згустків із прямокутним діелектричним хвилеводом. Виконане нами 3D-моделювання показало лінійне зростання амплітуди поздовжнього електричного поля на вихідному торці хвилеводу з довжиною взаємодії, що перебуває в гарній відповідності до експериментально отриманої залежності. Досліджувалися хронологічні залежності поздовжнього електричного поля поблизу вихідного торця хвилеводу на осі системи, отримані й проаналізовані спектральні характеристики коливань поля. Проведені дослідження призводять до кращого розуміння фізичних процесів, що відбуваються в кільватерному діелектричному прискорювачі.